Identification of a pathogenic SDHD mutation in a Chinese family with hereditary head and neck paraganglioma: implications for genetic counseling and management - Pu Wang; Liming Gao; Wenyang Zhang; Rui Guo; Yin Xia (World Journal of Surgical Oncology)
Abstract Background This study aims to identify a pathogenic SDHD mutation associated with hereditary head and neck paraganglioma (HNPGL) in a Chinese family and to explore its implications for genetic counseling. Methods The study involved a family with 15 members spanning three generations. A 31-year-old patient (II-4) was diagnosed with a left parotid gland tumor and a right carotid body tumor, while both the father and elder sister had right carotid body tumors, and the third sister had bilateral carotid body tumors. Whole exome sequencing and Sanger sequencing were employed to identify candidate pathogenic variants. Genetic counseling was conducted for third-generation descendants to assess the likelihood of carrying the mutation and to guide future diagnosis and treatment. Results A nonsense mutation in the SDHD gene (NM_001276503:exon2:c.C64T: p.R22X) was identified in the patient and three other affected family members. Genetic counseling for the third generation revealed that only one child (III-4) carried the pathogenic mutation inherited from the patient’s third sister. Conclusion We identified a pathogenic mutation in SDHD in a Chinese HNPGL family, which is the second reported case of its kind. Our genetic counseling analysis for the third generation provided important information for the family and guidance for future diagnosis and treatment.